Characteristics of an Electrostatic Wiggler for Improved Free Electron Radiation - Kim, Dae-Wook; Kumar Jha, Vinaya; Ahn, Seungjoon; Oh, Tae-Sik; Seob Kim, Ho; Chul Kim, Young (Asian Journal of Chemistry, 2013)
Characteristics and structure of a free electron radiation module composed of an electron source and an electrostatic wiggler have been investigated through a simulation, especially focused on a planar type wiggler. In order to improve the efficiency of planar type wiggler in asymmetric operation mode, a simple modification in the wiggler structure is suggested and the improved performance of the modified wiggler system will be discussed.